A Novel Adjustable EndoButton Fixation Assisted by 3D Printing Technology for Tibiofibular Syndesmosis Injury: A Biomechanical Study - Zhang, Lei; Xu, Junjie; Tang, Xiangyu; Zhou, Xin; Li, Bingkun; Wang, Guoyou (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: The recommendations for surgical fixation of tibiofibular syndesmosis injuries are increasingly challenging for many clinical orthopedists, as international consensus has not been published for the optimal treatment of the injury. Thus, we have created a 3D-printed navigation template for a precise bone tunnel and a novel adjustable EndoButton fixation (NAE) for the ideal treatment. The purpose of this research was to evaluate the accuracy of the 3D-printed navigation template and explore the biomechanical performance of the NAE technique by comparing it with the intact syndesmosis, screw technique, and TightRope (TR) technique. Methods: Twenty-four human cadaveric legs were randomly allocated to four groups: the NAE group (n = 6), TR group (n = 6), screw group (n = 6), and intact group (n = 6). A personalized navigation template based on computed tomography scans was designed, and 3D printing models were generated for the distal tibiofibular syndesmosis. The NAE, TR, and screw group were performed via 3D-printed navigation template, respectively. All groups were tested under increasing loading forces including axial loading (from 100 N to 700 N) and torsional loading (from 1 N to 5 N), which were performed in different ankle positions. The displacements of the tibiofibular syndesmosis were analyzed using the Bose Electroforce 3510-AT biomechanical testing equipment. Results: Surgical fixations were conducted successfully through a 3D-printed navigation template. Both in axial or torsional loading experiments, no statistically significant difference was observed in the displacements among the NAE, TR, and intact groups in most situations (p > 0.05), whereas the screw group demonstrated obviously smaller displacements than the abovementioned three groups (p < 0.05). Conclusion: The 3D printing technology application may become beneficial and favorable for locating and making the bone tunnel. Also, the NAE fixation provides the performance of complete ligaments; it also restores physiologic micromotion and avoids insufficient or excessive reduction when compared to the TR and screw technique. This may offer a new fixation for the treatment of tibiofibular syndesmosis injuries that is desirable for clinical promotion.